(untitled) (Revista Brasileira de Ciências Farmacêuticas, 2007)
Chocolate is a product widely consumed throughout the world that has seen generally increasing production trends over the last years. Making chocolate requires an understanding of how the consumer perceives it. The preferred type of chocolate varies from country to country. The different tastes and uses for chocolate reflect the histories of the industry in different places. The taste of chocolate is partially determined by the chemistry of the product. Taste depends on the release of flavor compounds in the mouth and nose, while perceived texture is a function of the way in which the material melts and breaks up in the mouth. Most chocolates that are available on the market throughout the world are made from very similar ingredients, yet have very different flavors. Some manufacturers have specific house flavors, and very often this is due to specific changes during the manufacturing process, where changes in holding times, acidity and temperature can give rise to very different flavors in the final chocolate. For this reason, chocolate manufacturing conditions are often kept a closely guarded secret. The ingredients used in chocolate and confectionery products have an important role in consumers acceptance and presentation of the product.